Relationship between Self-Differentiation and Mental Health in Veterans and Disabled Persons - M. Kiyani; T. Shirvani; E. Khandan (Afarand Scholarly Publishing Institute, 2014)
Aims: Self-differentiation means how much a person has got emotional independence in her family and her independence has decreased. Veterans and disabled persons relationship with their families is very important because how much they achieve self-differentiation from their families may they face with some conflicts in their life that they are unable to solve them that can cause some mental health disorders. The present study was done to investigate the correlation between self-differentiation and mental health in veterans and disabled persons. Materials & Methods: This descriptive-correlational study was done on 200 athlete veterans and disabled persons of Charmohal and Bakhtiyari in 2013 and due to the limitations of the sample, all members were selected as samples. Data were collected using two Skowron and Friedlander self-differentiation and Goldberg general health questionnaires. To data analyze, Pearson correlation coefficient and simultaneous multiple regression analysis using SPSS 21 software was done. Findings: The mean total score of self-differentiation questionnaire in veterans and disabled persons was 149.81±29.99 and the mean total score of the mental health was 61.41±20.62. There was a significant and direct correlation between self-differentiation and my position subscale with mental health and its subscales. Also there was a significant and diverse correlation between level of emotional reactivity, emotional faults and fusion with others with mental health and its subscales. Conclusion: Raising the veterans and disabled persons differentiation level, increasing the mental health level